Pemeliharaan Ikan Beronang, Siganus gutatus sebagai Biokontrol Perkembangan Lumut, Chaetomorpha sp. dan Enteromorpha intestinalis di Tambak - Suharyanto Suharyanto (Jurnal Perikanan Universitas Gadjah Mada, 2009)
The aim of this research was to control the growth of green algae (Chaetomorpha sp and Enteromorpha intestinalis) by rabbit fish (Siganus gutatus) reared in brackishwater ponds in different stocking density. The research was conducted in the Research Station of Research Institute for Coastal Aquaculture, Marana, Maros South Sulawesi for 100 days. Nine brackishwater ponds in the size 100 m2 (3 ponds), 125 m2 (3 ponds) and 150 m2 (3 ponds) with the green algae growth were used respectively in this research. Group randomized design was used in this research. This research use three stocking density of rabbit fish in thriplicates that were (A) 20 ind/100m2 , (B) 30 ind/100 m2 (40 ind/125 m2), and (C) 40 ind/100m2 (60 ind/150 m2), respectively. The rabbit fish used in this research were 9.1+ 0.8 cm in length and 15+ 0,6 g in body weigth. The monitored variables were body length and weigth, survival rate and water quality. The result showed that the effect of stocking density not significantly different on the growth of body length and weight and survival rate of rabbit fish reared in brackishwater pond (P>0.05), but significantly different on the productivity of rabbit fish (P<0.05). Green algae growth in the brackishwater ponds could be controlled with the rearing of rabbit fish in the stocking density 20 - 40 ind/100 m2.